2020
DOI: 10.1002/chem.201905781
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Aspects of Xanthene Dye Aggregation on the Surfaces of Nanocluster Polyoxometalates: H‐ to J‐Aggregate Switching

Abstract: The induced aggregation of the xanthenedye rho-damineB (RhB) on metal oxide centers belonging to the highly symmetric surfaces of precise nanoscale templates with Keplerate (Mo 132 )o rtoroidal (Mo 138 )s tructures has been studied. With the joint use of the Langmuir isotherma nd full Stern-Volmer models, the thermodynamic reasons for dye adsorption on the nanocluster surface, such as amixture of monomer,H -aggregate (H-dimer), and J-aggregate forms (which can coexist or switch one into another under the exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…An integrated approach to the study of the physicochemical properties of the Mo 132 and Mo 72 Fe 30 Keplerate POMs [138,161,301], as well as the possibility of their association with bioactive molecules and fluorescent dyes, made it possible to formulate the concepts [302][303][304] of creating long-time-drug-releasing systems (LDRS) with a function LDRS will be based on the release of molecules of bioactive (medicinal) substances, initially bound with POM, and the intensification of fluorescent labels luminescence. The release occurs at the normal pH (7.2-7.4) of the body environment, due to the POM destruction.…”
Section: Prospects For the Creation Of Pom-based Releasing Systems Wimentioning
confidence: 99%
See 2 more Smart Citations
“…An integrated approach to the study of the physicochemical properties of the Mo 132 and Mo 72 Fe 30 Keplerate POMs [138,161,301], as well as the possibility of their association with bioactive molecules and fluorescent dyes, made it possible to formulate the concepts [302][303][304] of creating long-time-drug-releasing systems (LDRS) with a function LDRS will be based on the release of molecules of bioactive (medicinal) substances, initially bound with POM, and the intensification of fluorescent labels luminescence. The release occurs at the normal pH (7.2-7.4) of the body environment, due to the POM destruction.…”
Section: Prospects For the Creation Of Pom-based Releasing Systems Wimentioning
confidence: 99%
“…The release occurs at the normal pH (7.2-7.4) of the body environment, due to the POM destruction. The main principle LDRS are based on is the discovered effect [302][303][304] of a fluorescent label (xanthene dye rhodamine-B, RhB) inactivation on the POM surface due to charge transfer processes. This makes it possible to monitor the drugs release due to the intensification of the signal from the fluorescent labels [305,306] incorported in the applied LDRS.…”
Section: Prospects For the Creation Of Pom-based Releasing Systems Wimentioning
confidence: 99%
See 1 more Smart Citation
“…[32] In contrast, the non-symmetrical J aggregates are fluorescent and absorb at ~570 nm, whereas the monomers absorb near ~550 nm. [32,33] The aqueous solution of the βCD/Rho complex at alkaline pH is red-colored and visibly fluorescent. Specifically, at the present working pH ~9.5, the βCD/Rho complex in water with 2 eq of NMM shows strong absorption in the visible region (λ max = 555 nm, Figure S10).…”
Section: Exploration Of Inclusion Binding Of Rhodamine B With βCd and 6-monoamino-6-monodeoxy-βcd (Bmνη 2 )mentioning
confidence: 99%
“…templates) for the supramolecular design of functional materials. 2,3 Due to electrostatic forces, hydrogen bonding, van der Waals interactions and ligand exchange, 4 a POM's surface can be flexibly tuned with a variety of organic molecules to produce hybrids for different applications: porphyrin-sensitized hydrogen evolution, 5 "metal-oxide/dye" interface modeling, 2,6 NO donors, 7 drug release, [8][9][10] selective membranes, 11 magnetic nano-capsules, 12 contrast agents for magnetic resonance imaging (MRI), 13 liquid crystal design, 14 "host-in-host" supramolecular core-shell-type systems with cyclodextrins 15 and superlattice formation. 3 Furthermore, a recent study on the influence of the cooperative phenomenon on volatile molecule sorption into giant POMs showed that they can be used as nanoscaled molecular-separating units.…”
Section: Introductionmentioning
confidence: 99%